Kinetic and kinematic analysis of the leg positioning in the freestyle track start in swimming - Carradori, S.; Burkhardt, D.; Sinistaj, S.; Taylor, W. R.; Lorenzetti, S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
In swimming competitions, the track start is an important part of the race. The aim of this study was to assess and compare the relative positioning of the dominant leg in the preferential freestyle track start. The data was collected using the (Kistler) Performance Analysis System for Swimming (PAS-S) that includes a force measurement and motion analysis system. The results taken from 15 high level competitive swimmers showed that 67.7 % of the subjects naturally position their dominant leg in front. Starting with the dominant leg in front (6.67±0.24) was significantly (p < 0.001) faster than in the rear position (7.25±0.23). However swimmers had faster starts when using their preferential track start. Detailed analysis of the swimming start and the footedness allows coaches and athletes to train the fastest starting technique.